The changing epidemiology of invasive Haemophilus influenzae disease: Emergence and global presence of serotype a strains that may require a new vaccine for control - Tsang, Raymond S.W.; Ulanova, Marina (Vaccine, 2017)
•Global presence of Haemophilus influenzae serotype a (Hia).•Causes meningitis, bacteremic pneumonia, septic arthritis, epiglottitis.•High prevalence of invasive disease in indigenous children under five years old.•Genetics of Hia and clinical Hia diseases are very similar to Hib and Hib diseases.•Development of a Hia conjugate vaccine is a desirable public health investment. More than two decades after the implementation of the Hib conjugate vaccine in North America, Haemophilus influenzae serotype a (Hia) has emerged as a significant cause of invasive disease in Indigenous communities. However, little is known about the global presence of this pathogen. We interrogated the H. influenzae Multi-Locus Sequence Typing (MLST) website (https://pubmlst.org/hinfluenzae/) by selecting for serotype a records. We also updated our previous literature review on this subject matter. Hia has been reported from at least 35 countries on six major continents. However, most Hia diseases were associated with Indigenous communities. Clonal analysis identified two clonal populations with one typified as ST-23 responsible for most invasive disease in North America and being the predominant clone described on the H. influenzae MLST website. Incidence of invasive Hia disease in Indigenous communities in North America are similar to the rates of Hib disease reported prior to the Hib conjugate vaccine era. Hia causes severe clinical diseases, such as meningitis, septicaemia, pneumonia, and septic arthritis with case-fatality rates between 5.6% and 33% depending on the age of the patient and the genetic makeup of the Hia strain. Although invasive Hia disease can be found globally, the current epidemiological data suggest that this infection predominantly affects Indigenous communities in North America. The clinical disease of Hia and the clonal nature of the bacteria resemble that of Hib. The high incidence of invasive Hia disease in Indigenous communities, along with potential fatality and severe sequelae causing long-term disability in survivors, may support the development of a new Hia conjugate vaccine for protection against this infection similar in design to the one introduced in the 1990s to control invasive Hib disease.